'The urge to know about the roots is just human, I guess': Vietnamese Memories and Clément Baloup, an interview. Issue 1 (15th March 2022) - Gusain, Abhilasha; Jha, Smita
Abstract : In this interview, Clément Baloup addresses the varied aspects of his two graphic narratives, Vietnamese Memories: Leaving Saigon and Vietnamese Memories: Little Saigon (originally written in French). He talks about his choice of the medium, translation of his works to English and Baloup's role in it, illustration and colouring style, organisation of the two volumes, Vietnamese history and diaspora, his influences, and the recent project.